Candidate Genes for Age at Menarche Are Associated With Uterine Leiomyoma - Ponomarenko, Irina; Reshetnikov, Evgeny; Polonikov, Alexey; Verzilina, Irina; Sorokina, Inna; Yermachenko, Anna; Dvornyk, Volodymyr; Churnosov, Mikhail (Frontiers in Genetics, 2021)
Age at menarche is an important marker of the pubertal development and function of the hypothalamic-pituitary-ovarian system. It was reported as a possible factor for a risk of uterine leiomyoma (UL). However, while more than 350 loci for age at menarche have been determined by GWAS, no studies of these loci for their association with UL have been conducted so far. In this study were analyzed fifty two candidate loci for age at menarche for possible association with UL in a sample of 569 patients and 981 controls. The results of the study suggested that 23 out of the 52 studied polymorphisms had association with UL. Locus rs7759938 LIN28B was individually associated with the disease according to the dominant model. Twenty loci were associated with UL within 11 most significant models of intergenic interactions. Nine loci involved in 16 most significant models of interactions between SNP, induced abortions, and chronic endometritis were associated with UL. Among the 23 loci associated with UL, 16 manifested association also with either age at menarche (7 SNPs) or height and/or BMI (13 SNPs). The above 23 SNPs and 514 SNPs linked to them have non-synonymous, regulatory and eQTL significance for 35 genes, which play roles in the pathways related to development of the female reproductive organs and hormone-mediated signaling (FDR≤0.05). This is the first study reporting associations of candidate genes for age at menarche with UL.